Antiadhesive and antibacterial properties of pillar[5]arene-based multilayers. Issue 72 (23rd August 2018) - Barbera, Lucia; De Plano, Laura M.; Franco, Domenico; Gattuso, Giuseppe; Guglielmino, Salvatore P. P.; Lando, Gabriele; Notti, Anna; Parisi, Melchiorre F.; Pisagatti, Ilenia
Abstract : Carboxylato-pillar[5]arene/poly(allylamine hydrochloride) multilayer films loaded with antibiotics are shown to be effective in drastically reducing the surface adhesion of bacteria. Abstract : A new type of coating, based on carboxylato-pillar[5]arene/poly(allylamine hydrochloride) multilayer films, for the sustained release of antibiotics with in vitro antiadhesive and antimicrobial activity against Gram-positive and Gram-negative bacteria is described.